Verticillium longisporum infection induces organ-specific glucosinolate degradation in Arabidopsis thaliana - Witzel, Katja; Hanschen, Franziska S.; Klopsch, Rebecca; Ruppel, Silke; Schreiner, Monika; Grosch, Rita (Frontiers in Plant Science, 2015)
The species Verticillium represents a group of highly destructive fungal pathogens, responsible for vascular wilt in a number of crops. The host response to infection by V. longisporum at the level of secondary plant metabolites has not been well explored. Natural variation in the glucosinolate (GLS) composition of four Arabidopsis thaliana accessions was characterized: the accessions Bur-0 and Hi-0 accumulated alkenyl GLS, while 3-hydroxypropyl GLS predominated in Kn-0 and Ler-0. With respect to GLS degradation products, Hi-0 and Kn-0 generated mainly isothiocyanates, whereas Bur-0 released epithionitriles and Ler-0 nitriles. An analysis of the effect on the composition of both GLS and its breakdown products in the leaf and root following the plants' exposure to V. longisporum revealed a number of organ- and accession-specific alterations. In the less disease susceptible accessions Bur-0 and Ler-0, colonization depressed the accumulation of GLS in the rosette leaves but accentuated it in the roots. In contrast, in the root, the level of GLS breakdown products in three of the four accessions fell, suggestive of their conjugation or binding to a fungal target molecule(s). The plant-pathogen interaction influenced both the organ- and accession-specific formation of GLS degradation products.